2007
DOI: 10.1086/518366
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Simulation of 11-15 μm Spectra Associated with Polycyclic Aromatic Hydrocarbon Molecules

Abstract: We have obtained 11-15 mm spectra of thin films of hydrogenated amorphous carbon assembled from carbon nanoparticles. Well-defined, narrow features similar to the interstellar emission bands attributed to polycyclic aromatic hydrocarbons (PAHs) are observed at 11.3, 12, 12.8, 13.5, and 14.2 mm. These features are reproduced in many samples prepared under a variety of conditions, indicating that they involve common molecular components. We suggest that these are based on compact ring structures such as coronene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Using ZEKE, we have studied four peri-condensed species including pyrene, benzo­[ a ]­pyrene, benzo­[ e ]­pyrene, and benzo­[ ghi ]­perylene as well as four cata-condensed species including triphenylene, tetracene, pentacene, and chrysene. Our ZEKE data, supplemented by matrix isolation spectroscopy and other excitation and fluorescence spectroscopy, , allow for a comprehensive analysis of the vibrational states of cationic PAHs. These experimental results can further benchmark theoretical calculations and astrophysical modeling. , …”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Using ZEKE, we have studied four peri-condensed species including pyrene, benzo­[ a ]­pyrene, benzo­[ e ]­pyrene, and benzo­[ ghi ]­perylene as well as four cata-condensed species including triphenylene, tetracene, pentacene, and chrysene. Our ZEKE data, supplemented by matrix isolation spectroscopy and other excitation and fluorescence spectroscopy, , allow for a comprehensive analysis of the vibrational states of cationic PAHs. These experimental results can further benchmark theoretical calculations and astrophysical modeling. , …”
Section: Introductionmentioning
confidence: 69%
“…These experimental results can further benchmark theoretical calculations and astrophysical modeling. 40,41 In this work, we report resonantly enhanced multiphoton ionization (REMPI) spectroscopy of the first electronically excited state S 1 as well as ZEKE spectroscopy of the cationic state D 0 of benzo[h]quinoline (BhQ). We compare the spectroscopic features of BhQ with those of two isoelectronic systems phenanthrene and anthracene and comment on the unique contribution of the nitrogen atom.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Plateaulike features are produced by small particles because inter-and intra-molecular interactions within the material perturb the individual bands arising from the fundamental vibrations of the species making up the particles, shifting and broadening them. This results in band "smearing" across the regions normally associated with the fundamental modes (see, e.g., Morterra & Low 1983;Lee & Wdowiak 1993;Colangeli et al 1995;Baratta et al 1996;Schnaiter et al 1998;Mennella et al 1999Mennella et al , 2003Furton et al 1999;Hu & Duley 2007;Jones 2012aJones , 2012bJones , 2012c. If the particles are small enough, they produce broad emission features in the regions of the fundamental vibrational modes and thus are likely contributors to the plateaus that underly the well-known emission features.…”
Section: Discussionmentioning
confidence: 99%
“…They are caused by CH out-of-plane bending modes of PAHs. Laboratory studies of thin HAC films assembled from carbon nanoparticles conducted by Hu & Duley (2007) have shown that the spectra in the range from 11 μm to 15 μm show features similar to the interstellar emission bands of PAHs at 11.3,12,12.8,13.5, and 14.2 μm. They suggested that these bands might be attributed to compact ring structures such as coronene (C 24 H 12 ), which has peripheral substitutions with additional aromatic rings or sp, sp 2 -bonded carbon chains.…”
Section: Introductionmentioning
confidence: 98%